Overview on differential scanning calorimetry applications for early stage of cancers: brief report - Hoda Keshmiri-Neghab (Tehran University Medical Journal, 2016)
Background: Cancer is the most common cause of death in the world, and it incidence has been increasing for many years in economically developed countries. Early detection of cancers greatly increases the chances for successful treatment. So finding cancers before they start to cause symptoms is a most effective treatment. Recent studies have proposed that blood plasma contains a rich source of disease biomarkers for detecting, diagnosing and monitoring diseases. While some researchers have dismissed the low molecular weight serum peptidome as biological trash, recent work using differential scanning calorimetry has indicated that the peptidome may reflect biological event and contain diagnostic biomarkers.